Magnetic resonance imaging findings of xanthogranulomatous salpingo-oophoritis: A case report - Koichi Ito, MD; Kazuyuki Ohgi, MD; Manabu Yamada, MD; Akira Toyoshima, MD; Toshio Kumasaka, MD; Kensuke Suzuki, MD; Yukari Namiiri, MD; Akiyoshi Yamashita, MD; Hiroyuki Yokote, MD; Ko Matsushita, MD; Yuko Naraoka, MD; Tatsuki Ono, MD; et al. (Radiology Case Reports)
Xanthogranulomatous salpingo-oophoritis is an extremely rare disease that can be confused with adnexal malignancy. Few reports have described the diffusion-weighted imaging features of this disease. A 56-year-old woman presented with abdominal pain and was referred to our hospital. Magnetic resonance imaging showed a left adnexal mass extending to the uterus and the rectum. The solid component of the mass showed intense contrast enhancement on contrast-enhanced fat-saturated T1-weighted image. The component showed hypointensity on diffusion-weighted image and did not show restricted diffusion on the apparent diffusion coefficient map. The possibility of a malignant adnexal tumor was considered preoperatively because the mass had extended to the surrounding organs. The patient underwent surgery, and the postoperative pathological diagnosis was xanthogranulomatous salpingo-oophoritis. Although xanthogranulomatous salpingo-oophoritis extending to the surrounding organs may be confused with adnexal malignancy, the contrast-enhanced component of the mass without restricted diffusion could aid in the correct preoperative diagnosis and lead to less radical surgery.